Community empowerment in overcoming environmental health problems in Padukuhan Sawit Bantul: . - Kasjono, Heru Subaris; Rois, Ibn; Nugraha, Aliya Reggi; Utari, Devi; Clorinda, Nabila; Novita, Shella; Latifah, Tsalis Nanda; Widianto, Wahyu; Widiarto, Elvi Sandra (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Community empowerment is an effort to develop the potential of knowledge, skills, attitudes and accessibility to encourage and increase public awareness which aims to form community self-reliance. Community empowerment activities are carried out in Padukuhan Sawit. Community empowerment is a series of activities consisting of problem presentation activities, Community Self Survey (CSS) or Self-Introduction Survey (SMD), cadre training and finally dissemination by cadres. The purpose of this activity is so that the Padukuhan Sawit community becomes more empowered in overcoming environmental health problems. The method used in this activity is a qualitative approach and observation. The results of the activity show that the community is more willing and able to solve existing environmental health problems independently.